a) x+8,5=21,7
x = 21,7 - 8,5
x= 13,2
Vậy x= 13,2
b) 3/5x - 1/3 = 4/3
3/5x = 4/3+1/3
3/5x= 5/3
x = 5/3 : 3/5
x = 5/3 . 5/3
x= 25/6
Vậy x= 25/6
c) x-3/10 = 7/15 . 3/5
x-3/10= 7/25
x = 7/25 + 3/10
x = 14/50+ 15/50
x = 29/50
Vậy x=29/50
d) 1/2-1/2:x=3/4
1/2 : x =1/2-3/4
1/2 : x = 2/4-3/4
1/2 : x= -1/4
x= 1/2 : (-1/4)
x=-2
Vậy x= -2
e) -3/4 - x = =-7/12
x = -3/4 - (-7/12)
x = -9/ 12 +7/12
x= -1/6
Vậy x= -1/6
f) x+ 3/5 = 1/15
x = 1/15-3/15
x = -2/15
Vậy x= -2/15
g)3/4+1/4x= 5/8
1/4x= 5/8- 3/4
1/4x= 5/8-6/8
1/4x= -1/8
x= -1/8 : 1/4
x= -1/8 . 4
x= -1/2
Vậy x= -1/2
h) x- 3/8 = -5/7
x = -5/7 + 3/8
x = - 40/56 + 21/56
x = -19/56
Vậy x= -19/56
i) 7/2 - 11/5x= 1/5
11/5x = 7/2 - 1/5
11/5x = 35/10 - 2/10
11/5x=33/10
x= 33/10 : 11/5
x = 33/10 . 5/11
x= 3/2
Vậy x= 3/2